Khaled Abou El Fadl’s Perspective on Hadith Hermeneutics - Syamsuddin; Ahmad, Miladu Ahadi; Sumbulah, Umi (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
This article discusses the method of hadith hermeneutics according to Khaled M. Abou El-Fadl. El Fadl's academic concern is related to the authoritarianism of fatwas issued by several ulama and fatwa institutions. These fatwas are considered authoritarian and discriminatory towards women, seem rigid, and can’t adapt to the times. This authoritarianism phenomenon appears due to methodological errors in understanding legal texts, and the absence of negotiations between the text, the author, and the reader, each of whom has problems. Therefore, Khaled offers a hermeneutic method that consists of three things: text competence, meaning determination, and the concept of representation in Islam. If these three elements are met, then the fatwas of Islamic law produced by the ulama are authoritative, authoritarian, and discriminatoryThis article discusses themethod of hadith hermeneutics according to Khaled M. Abou El Fadl. El Fadl's academic concern is related to the authoritarianism of fatwas issued by several ulama and fatwa institutions. These fatwas are considered authoritarian and discriminatory towards women, seem rigid, and not adaptable to the times. This authoritarianism phenomenon appears due to methodological errors in understanding legal texts, and the absence of negotiations between the text, the author, and the reader, each of which has problems. Therefore, Khaled offers a hermeneutic method that consists of three things: text competence, meaning determination, and concept of representation in Islam. If these three elements are met, the fatwas of Islamic law produced by the ulama will be authoritative, authoritarian, and discriminatory. This research contributes to academic discourse by offering a nuanced perspective on the hermeneutics of hadith and fatwa production.